Commercial And Technical Realities Of Deep Ocean Mining - Jon Machin (International Marine Minerals Society, 2004)
?ORE? is defined as ?mineral/s that can be mined at a profit?. So, what is ORE at 2,000 m water depth? Is it 5% Copper or 1.8% Nickel/Cobalt? One of the key factors that determine what is ORE, profitable or not, is the cost of mining and extraction. Therefore a determination of ORE requires a commercial and technical appreciation of both sea bed mining equipment and mining options. Perry Slingsby Systems (PSS) have built more remotely operated submarine work vehicles, including 900HP trenching machines, than any other company. With Nautilus Minerals, PSS have been studying a range of deep ocean mining solutions. This paper discusses the commercial and technical issues of various extraction techniques applicable to deep ocean mining from 1,500 m to 5,000 m water depth. Issues such as the rate of extraction, (i.e. tons per hour) is a key economic component and is often constrained by the design and horsepower of the miner. Likewise the design itself of the mining machine and cutting heads can determine the size of material produced which impacts on methods of lifting the ore to surface. Issues such as overburden, sea floor conditions, style of mineralization and physical properties of the ore, obviously affect the selection of appropriate mining machine configuration.